Metalworkers and their Tools Symbolism, Function, and Technology in the Bronze and Iron Ages - Boutoille, Linda; Peake, Rebecca (2024)
Metalworkers and their Tools brings together 12 papers by 22 authors from the "Metools" international symposium organised in at Queens University, Belfast in June 2016 as part of the HardRock project "Between a Rock and a Hard Place: context, function, and choice of early metalworking tools on Europe's Atlantic façade" (Marie Skłodowska Curie, No. 623392) and the "Metal Ages in Europe" commission of the International Union of Pre- and Protohistoric Sciences (UISPP). Its aim was to shine a spotlight on the tools of the metalworker and to follow their evolution from the beginning of the Bronze Age through to the Iron Age, as well as the place held by metalworking and its artisans in the economic and social landscape of the period.